Josefina javelina : a hairy tale - Lowell, Susan, 1950- (Rising Moon, 2005)
Josephina, a javelina who dreams of becoming a famous ballerina, heads for California hoping to be discovered, but her cousin Angelina takes her to a talent agent who looks strangely familiar.